H. Ploeg (met ambtsketen) ontvangt St. Nicolaas voor het stadhuis van Utrecht. Rechts naast hem: A.C. Ploeg (1959)
H. Ploeg (met ambtsketen) ontvangt St. Nicolaas voor het stadhuis van Utrecht. Rechts naast hem: A.C. Ploeg.